KEJADIAN TOXOCARIASIS PADA KUCING BERDASARKAN RAS KUCING DI DAERAH ISTIMEWA YOGYAKARTA - , NURHUDA; , Dr. drh. R. Wisnu Nurcahyo, ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toxocariasis is a parasitic nematode diseases known to infect cats. This study aimed to determine the incidence of toxocariasis in cats in Yogyakarta. Samples from 280 cat faeces were used in this study. The owners were given a questionnaire containing general examination data, cat sex, age, race, vaccination status, the origin of the cat, system maintenance, the feed, and the frequency of diarrhea. Faecal samples were examined in the Parasitology Laboratory of the Faculty of Veterinary Medicine, University of Gadjah Mada, the native method and centrifuges analyses, then the data obtained in the examination were analyzed descriptively. The results showed there were 7 of 280 samples found worm eggs Toxocara sp. Domestic cats infected with Toxocara sp. there were 4 cats, 2 Angora cats, and Persian cat. Based on these results it can be concluded that the level of infestation of Toxocara sp. in cats in Yogyakarta 2.5% (7/280), domestic cats 0.051% (4/78) is higher than the Persian cat 0.0069% (1/144) and highest in the Angora cat 0.125% (2/16).